Preparation of Industrial Minerals - The Firing of Rotary Kilns with Powdered Coal (Mining Tech., Sept., 1946, T.P. 2042) - W. C. Knoblaugh (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1948)
Rotary kilns are adaptable to many fuels, but this paper deals principally with the use of powdered coal. The observations and conclusions presented are based on rotary kilns used in the manufacture of basic refractories for steel furnaces. Solid fuels are pulverized for two principal reasons: (I) ease of control, and (2) rapidity of combustion. By the use of pulverized coal, the operator can increase or decrease the fuel supply by small increments and with very little time lag between the change of control and the resultant change in the flame. This is extremely important in this type of furnace, as the temperature range for maturing the clinker is very narrow. By fine grinding, it is possible to increase the rate of burning of the coal, thereby liberating great quantities of heat within a small space in a short time. Under given conditions, temperature is a measure of the heat liberated per unit of time. To attain the temperatures of 2950° to 3150ºF., which are encountered in the manufacture of various steel-furnace refractories, it is estimated that it is necessary to liberate 125,000 to 175,000 B.t.u. per cubic foot of the burning zone per hour. The manufacture of dolomitic refractories is a ceramic process and, as is true in most such processes, the material must be subjected to a certain critical temperature for a certain length of time in order to complete the reaction. If the time of reaction is reduced, the temperature must be increased; in other words, if the rate at which the material flows through the hot zone of the kiln is increased, the temperature of the hot zone must be increased to compensate for this shorter exposure to the flame. Firing with Pulverized Coal Fig. I is a line drawing of a rotary kiln with the attendant equipment indicated in their relative positions. The kiln proper consists of a sloping, refractory-lined steel tube rotating slowly about its longitudinal axis (0.75 r.p.m.), and is countercurrent in operation in that the raw feed is introduced at the stack end and gradually approaches the zone of highest temperature at the lower end, where the fuel is introduced. Before 1930, the usual method of firing a rotary kiln was to store the coal in the pulverized form and then feed from this storage to the kiln as needed. This proved unsatisfactory and dangerous because of dust explosions and the inability to obtain an even feed to the kiln caused by arching of the coal in storage and flooding of the coal feeders. In later years the practice has been to store the raw coal and grind it as it is needed. Such a layout is indicated in Fig. I. The coal is stored in bins, charged from the top and drawn from the bottom into recording scales and then into some type of unit pulverizer. There are a number of good pulverizers .on the market, each incorporating features that the manufacturer considers outstanding.